The Structure and Content Analysis of ‘Al-Qanon al-Saghir’: A Descriptive Analysis - Hanieh Ghasemi; Sharareh Sharififar; Hassan Azari; Shekoofeh Sharififar (Journal of Research on History of Medicine, 2023)
Among the historical traditional medical texts, there are several hand-written manuscripts with the same structure and format on one topic. Two versions of these hand written manuscripts are under the titles of Al-Kafi Fi Al-Teb and Al-Kefaye Fi Elm Al-Teb, or briefly Al-Kefayeh which in the early sources is also referred to as Al-Qanon al-Saghir, attributed to Ibn Mandevaih. On the other hand, other versions of the Al-Qanon al- Saghir were attributed to Avicenna. Since it seems unlikely that these quite similar versions belong to two authors, it is necessary to figure out the actual writer of the work. This paper is a descriptive analysis of the existing evidence about Al-Qanon al-Saghirh and written scripts,  comparing their structure and contents to similar works of Ibn Mandevaih, and Avicenna, to determine whether the author is the former or the latter, or both. After investigating historical documents, the investigators found that Al-Qanon al-Saghir was attributed to Ibn Mandevaih in early works and to Ibn-Sina in later works. The he similarities found in the structure and content of the two versions make it difficult to convince the researchers to consider each text as a separate book written by different authors. Moreover, contradictory findings presented in Al-Qanon al-Saghir to Avicenna’s famous works indicated that this book belongs to Ibn Mandevaih. The brief and comprehensive al-Qanon al-Saghir is not the summary of the extensive al-Qanon Fi Teb medical textbook by Avicenna but rather an entirely different book written by  Ibn Mandevaih.